2000
DOI: 10.2737/pnw-gtr-485
|View full text |Cite
|
Sign up to set email alerts
|

Source habitats for terrestrial vertebrates of focus in the interior Columbia basin: broadscale trends and management implications. Volume 1—Overview.

Abstract: We defined habitat requirements (source habitats) and assessed trends in these habitats for 91 species of terrestrial vertebrates on 58 million ha (145 million acres) of public and private lands within the interior Columbia basin (hereafter referred to as the basin). We also summarized knowledge about species-road relations for each species and mapped source habitats in relation to road densities for four species of terrestrial carnivores. Our assessment was conducted as part of the Interior Columbia Basin Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(159 citation statements)
references
References 0 publications
8
151
0
Order By: Relevance
“…For gray wolves, both Mech et al (1988) and Thiel (1985) found that when road densities exceed about 1.6 km/0.9-km-radius circle (1 mi/mi 2 ), wolves avoided or were displaced from areas. Mladenoff et al (1995) found road density to be the major Claar et al 1999;Hood and Parker 2001;Jonkel 1980;Kasworm and Manley 1990;Linnell et al 2000;Mace andWaller 1996, 1998;Mace et al 1996Mace et al , 1999Mattson et al 1987;McLellan andShackleton 1988, 1989;Puchlerz and Servheen 1998;Weaver et al 1987;Wisdom et al 2000. b Sources: Banci 1994, Buskirk 1999, Claar et al 1999, Koehler and Aubry 1994, McKelvey et al 2000, Ruediger et al 2000.…”
Section: Information Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…For gray wolves, both Mech et al (1988) and Thiel (1985) found that when road densities exceed about 1.6 km/0.9-km-radius circle (1 mi/mi 2 ), wolves avoided or were displaced from areas. Mladenoff et al (1995) found road density to be the major Claar et al 1999;Hood and Parker 2001;Jonkel 1980;Kasworm and Manley 1990;Linnell et al 2000;Mace andWaller 1996, 1998;Mace et al 1996Mace et al , 1999Mattson et al 1987;McLellan andShackleton 1988, 1989;Puchlerz and Servheen 1998;Weaver et al 1987;Wisdom et al 2000. b Sources: Banci 1994, Buskirk 1999, Claar et al 1999, Koehler and Aubry 1994, McKelvey et al 2000, Ruediger et al 2000.…”
Section: Information Gapsmentioning
confidence: 99%
“…c Sources: Brand and George 2001, Foppen and Reijnen 1994, Gutzwiller et al 2002, Hickman 1990, Hutto 1995, Keller and Anderson 1992, Miller et al 1998. d Sources: Buskirk and Ruggiero 1994Claar et al 1999;Powell 1979Powell , 1982Weaver 1993;Wisdom et al 2000. e Sources: Claar et al 1999;Heinenmeyer and Jones 1994;Powell 1979Powell , 1982Rosenburg and Raphael 1986;Weaver 1993;Wisdom et al 2000.…”
Section: Assessment Processes For Focal Speciesmentioning
confidence: 99%
“…These parameters influence stand productivity and species composition, as well as the density and growth of the understorey, which is a key determinant of habitat [4]. Estimation of canopy coverage is important in studies of species-habitat relationships (e.g., [5][6][7][8][9][10]) and also for land managers given the increasing emphasis on sustainable woodland management. The effective use of canopy data in ecological research, or to inform woodland management, demands that measurements are accurate, precise, and obtainable using a quick, easy, and inexpensive method [11].…”
Section: Introductionmentioning
confidence: 99%
“…Within this core of historical habitat, the current amount of source habitat has been reduced dramatically from historical levels by 91% in the Columbia Plateau and 85% in the Owyhee Uplands. Within the entire Interior Columbia Basin, overall decline in source habitats for this species (71%) was third greatest among 91 species of vertebrates analyzed (Wisdom et al 2000). Wing (1941) described the grasshopper sparrow as occupies the edge between the AgropyronPoa type and the Festuca-Agropyron type.…”
Section: Population and Distributionmentioning
confidence: 99%
“…Population Historic According to the ICBEMP terrestrial vertebrate habitat analyses, historical source habitats for grasshopper sparrow within our planning unit occurred primarily along the eastern portions of the Columbia Plateau Ecological Reporting Unit (ERU) and the northern portion of the Owyhee Uplands ERU with a small amount in the northern portion of the Great Basin (Wisdom et al 2000). Within this core of historical habitat, the current amount of source habitat has been reduced dramatically from historical levels by 91% in the Columbia Plateau and 85% in the Owyhee Uplands.…”
Section: Population and Distributionmentioning
confidence: 99%